Demand for energy in Southern India - National Council of Applied Economic Research (New Delhi, 1962)
The Role of energy in a nation's economy cannot be over-emphasized particularly in the context of industrial development. An assessment of the overall needs of energy of a country is important but a detailed study of regional demands is even more significant, if there are not to be any imbalances in the development of a vast country like India. It is the regional aspect on which emphasis was laid by Messrs. Burmah-Shell, when requesting the National Council of Applied Economic Research to assess the energy requirements of the Southern Region.
Keywords: Energy